2020
DOI: 10.1016/j.devcel.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Inflammasome Activity Controls Embryonic Hematopoietic Stem and Progenitor Cell Production

Abstract: Embryonic hematopoietic stem and progenitor cells (HSPCs) robustly proliferate while maintaining multilineage potential in vivo; however, an incomplete understanding of spatiotemporal cues governing their generation has impeded robust production from human induced pluripotent stem cells (iPSCs) in vitro. Using the zebrafish model, we demonstrate that NLRP3 inflammasome-mediated interleukin-1-beta (IL1β) signaling drives HSPC production in response to metabolic activity. Genetic induction of active IL1β or phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 111 publications
(149 reference statements)
4
75
0
Order By: Relevance
“…While not investigated here, our in vitro bioinformatics analysis also revealed an intriguing role for inflammatory signaling in HSPC formation in the context of EZH1 knockdown ( Figure S5 F). Our laboratory and others have shown that sterile inflammatory signaling regulates HSPC formation and expansion during development ( Espín-Palazón et al., 2014 ; Frame et al., 2020 ). Here, we saw an enrichment in inflammatory pathways, including interferon-α (IFNα), IFNγ, and tumor necrosis factor α (TNFα) following knockdown of EZH1 ; whether this is due to active EZH1 repression or simply reflective of an increase in committed HSPCs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…While not investigated here, our in vitro bioinformatics analysis also revealed an intriguing role for inflammatory signaling in HSPC formation in the context of EZH1 knockdown ( Figure S5 F). Our laboratory and others have shown that sterile inflammatory signaling regulates HSPC formation and expansion during development ( Espín-Palazón et al., 2014 ; Frame et al., 2020 ). Here, we saw an enrichment in inflammatory pathways, including interferon-α (IFNα), IFNγ, and tumor necrosis factor α (TNFα) following knockdown of EZH1 ; whether this is due to active EZH1 repression or simply reflective of an increase in committed HSPCs remains to be elucidated.…”
Section: Discussionmentioning
confidence: 94%
“…61 This assumption is grounded on the role of inflammatory cues in stem cell maintenance and tissue regeneration 62 as well as on the capacity of macrophages to produce and react to immune signals. 63 For instance, macrophage-mediated production of IL-1β and potentially of other cytokines 64 contributes to the emergence and adaptation to stress of stem cells, [65][66][67] while excessive inflammatory signaling impairs regeneration. 68,69 In this context, prostaglandin E 2 (PGE 2 ), a lipid derivative of arachidonic acid released by activated macrophages as well as by necrotic cells or by TME components, 70,71 orchestrates immune homeostasis during tissue repair and cancer.…”
Section: Tumor S Co -Op T the Homeos Tatic Role S Of Macrophag E S:mentioning
confidence: 99%
“…Bmp4 is expressed in the ventral aspect of the dorsal aorta and promotes the hematopoietic stem cell program, whereas the expression of Shh in the roof maintains the arterial program (Wilkinson et al, 2009). More recently, it was shown that myeloid cells (Espín-Palazón et al, 2014) and metabolic alterations that promote inflammasome-induced IL1β-signaling in macrophages enhance HSC production, and inflammasome inhibition results in decreased hematopoietic generation (Frame et al, 2020). Taken together, these observations indicate that the EHT is a complex process involving several key molecular players and different cell types.…”
Section: Teleosts or Bony Fish (Zebrafish)mentioning
confidence: 99%